PEMBERSIHAN RITUAL DAN SPIRITUALITAS: ANALISIS LUKAS 11:39 DALAM KONTEKS PERIBADATAN - Elvinniska Ndruru (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2023)
This article analyzes ritual and spiritual cleansing in the context of worship according to Luke 11:39. According to the Pharisees' point of view, religious traditions or rituals must be carried out to maintain holiness because the Pharisees are religious leaders, who have the power to teach other people in worship and determine the regulations for carrying out worship. One of them is washing your hands before eating. The act is considered a necessity to show purity. In reality, the religious rituals of the Pharisees were only to justify themselves, while their hearts were far from God. Christians perform ritual cleansing in worship. This tradition is not wrong; it can only result in a shift in the focus of worship. The desire to appear spiritual is a ritual cleansing many people can see. Spiritual cleansing is the most important thing to do. The method used in this research is a qualitative analytical-theological approach using a literature study method. This research concludes that Jesus' words to the Pharisees about cleaning the cup and plate contain a figurative meaning: the human body, namely the heart. The heart needs to be cleansed from all evil and hypocrisy.